2021
DOI: 10.1371/journal.pone.0241682
|View full text |Cite
|
Sign up to set email alerts
|

Development, validation, and pilot MRI safety study of a high-resolution, open source, whole body pediatric numerical simulation model

Abstract: Numerical body models of children are used for designing medical devices, including but not limited to optical imaging, ultrasound, CT, EEG/MEG, and MRI. These models are used in many clinical and neuroscience research applications, such as radiation safety dosimetric studies and source localization. Although several such adult models have been reported, there are few reports of full-body pediatric models, and those described have several limitations. Some, for example, are either morphed from older children o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 98 publications
0
9
0
Order By: Relevance
“…Our previous studies showed the MRI RF safety of the NeoNet using numerical simulation [19]. This study showed that the high-power MPRAGE heating was well below 2 • C. Our recent simulation study on EEG safety with an infant/toddler [55] also showed a similar finding based on the dielectric properties of the resistive traces in infants/toddlers for safe EEG-MRI [56], where thin film resistive traces reduced the RF heating at 3 T MRI within the safety guidelines by the FDA [57]. Thus, resistive traces may improve the safety of infant/toddler EEG-MRI, as shown by our SAR, and thermal safety [10,58], regardless of the sequence used.…”
Section: Mri Safetymentioning
confidence: 81%
See 1 more Smart Citation
“…Our previous studies showed the MRI RF safety of the NeoNet using numerical simulation [19]. This study showed that the high-power MPRAGE heating was well below 2 • C. Our recent simulation study on EEG safety with an infant/toddler [55] also showed a similar finding based on the dielectric properties of the resistive traces in infants/toddlers for safe EEG-MRI [56], where thin film resistive traces reduced the RF heating at 3 T MRI within the safety guidelines by the FDA [57]. Thus, resistive traces may improve the safety of infant/toddler EEG-MRI, as shown by our SAR, and thermal safety [10,58], regardless of the sequence used.…”
Section: Mri Safetymentioning
confidence: 81%
“…Thus, resistive traces may improve the safety of infant/toddler EEG-MRI, as shown by our SAR, and thermal safety [10,58], regardless of the sequence used. In this study, our target trace resistance of 10-15 kΩ was based on our recent study [55] in which we studied the safety using resistors of 10 kΩ, and the 5-15 kΩ industry standard. A lower resistance below 10 kΩ may affect the amount of RF-induced currents in the NeoNet traces inside a 3 T MRI, which could lead to both heating and greater B 1 artifacts.…”
Section: Mri Safetymentioning
confidence: 99%
“…Electromagnetic simulations were implemented in ANSYS Electronics Desktop 2020 R2 (ANSYS Inc., Canonsburg, PA). A pediatric body model consisting of average tissue, skull, brain, ribcage, and heart was created from segmented MRI images of a 29-month-old child (23) and post-processed to form a tetrahedral mesh for finite element simulations (see Figure 2). A model of a 16-rung high-pass birdcage coil with dimensions mimicking a Siemens 1.5 T Aera body coil was created based on technical specifications provided by the vendor and tuned to 63.6 MHz (24).…”
Section: Methodsmentioning
confidence: 99%
“…A human shaped head and torso phantom representing a pediatric patient was designed based on segmented MR images of a 29-months-old child [15] (Fig. 1).…”
Section: A Pediatric Phantom Preparationmentioning
confidence: 99%